Technology Entrepreneurship in the Russian Regions: Educational and Geographical Paths of Start-up Founders - Tolmachev, Dmitry Evgenievich; Chukavina, Kristina Vladimirovna (Economy of Regions, 2020)
Technology entrepreneurship is one of key research areas in the modern economy as fast-growing companies significantly contribute to the economic growth of the regions and Russia in general. Identifying factors influencing the emergence and success of start-ups could give the tools to support and stimulate entrepreneurship in this field. In this research, we collected and analysed data on technological start-ups founded in the past decade. We focused on identifying global start-ups, in which at least one of the founders was educated in Russia. The final sample includes more than 1000 start-ups of Russian origin. During the study, we discovered the main trends in the educational, geographical and sectorial paths of start-up founders. We hypothesise that the promotion of technical education in the regions, and the use of information technologies in business play a significant role in the development of technology entrepreneurship. The econometric analysis allowed us to determine regional factors influencing the emergence of successful start-ups in the region, as well as regional factors affecting the intention to establish a technology start-up in a country or a region differing from the place where they had obtained education. In the regions close to Moscow and relatively developed regions, the level of salaries for programmers is of significance. An entrepreneur’s desire to change a region or a country can be affected by the level of inventive activity in a region, the number of students of mathematical specialties, the distance to Moscow. Future studies can focus on a country analysis of the success factors of technology start-ups, an analysis of the world’s most attractive entrepreneurial start-up ecosystems, and the place of Russian technology entrepreneurs on the map of successful global start-ups.